Public administration and governance: a sector-level analysis of World Bank aid - Moloney, Kim (2009)
This article turns the question about socioeconomic development away from its usual goal of economic growth and argues that governance is another appropriate measure of economic development. Instead of econometric analyses of country-level data, this article shows how aggregating project-level data to a sector-based approach is a new methodological tool for determining whether project and policy objectives translate into improved governance. Using the World Bank's public administration, law and justice projects and panel-corrected time series, this article finds that the World Bank's public administration, law and justice projects inconsistently improve governance. - Reproduced.
Keywords: World Bank; Public administration